Hepato-gastric and spleno-mesenteric arterial trunks: anatomical variation report and review of literature - Mariani, Giulia A.; Maroni, Lorenzo; Bianchi, Lorenzo; Broccoli, Alessandro; Lazzarini, Enrico; Marchegiani, Giovanni; Mazzotti, Antonio; Mazzotti, Maria Carla; Billi, Anna Maria; Giuliani Piccari, Gabriella; Cocco, Lucio; Manzoli, Lucia (Italian Journal of Anatomy and Embryology, 2013)
The celiac trunk is one of the main arteries arising from abdominal aorta and supplies blood to several abdominal organs. The typical branching in left gastric, splenic and common hepatic arteries undergoes relatively frequent variations. The authors report a rare variation of the celiac trunk in a Caucasian cadaver, with a hepato-gastric and a spleno-mesenteric arterial trunks which arise from the abdominal aorta in a routine dissection of a 98-year-old male cadaver. Detailed knowledge of this kind of variations is important to plan and perform surgery in this district.